A Randomised Trial Examining Cardiovascular Morbidity and All-Cause Mortality 24 years Following General Health Checks: the Ebeltoft Health Promotion Project (EHPP). Issue 10 (28th October 2019) - Bernstorff, Martin; Deichgræber, Pia; Bruun, Niels Henrik; Dalsgaard, Else-Marie; Fenger-Grøn, Morten; Lauritzen, Torsten
Abstract : Introduction: Global prevalence of risk factors for cardiovascular disease (CVD) and all-cause mortality is increasing. Treatments are available but can only be implemented if individuals at risk are identified. General health checks have been suggested to facilitate this process. Objectives: To examine the long-term effect of population-based general health checks on CVD and all-cause mortality. Design and setting: The Ebeltoft Health Promotion Project (EHPP) is a parallel randomised controlled trial in a Danish primary care setting. Participants: The EHPP enrolled individuals registered in the Civil Registration System as (1) inhabitants of Ebeltoft municipality, (2) registered with a general practitioner (GP) participating in the study and (3) aged 30–49 on 1 January 1991. A total of 3464 individuals were randomised as invitees (n=2000) or non-invitees (n=1464). Of the invitees, 493 declined. As an external control group, we included 1 511 498 Danes living outside the municipality of Ebeltoft. Interventions: Invitees were offered a general health check and, if test-results were abnormal, recommended a 15–45 min consultation with their GP. Non-invitees in Ebeltoft received a questionnaire at baseline and were offered a general health check at year 5. The external control group, that is, the remaining Danish population, received routine care only. Outcome measures: HRs for CVD and all-cause mortality. Results: Every individual randomised was analysed. When comparing invitees to non-invitees within the municipality of Ebeltoft, we found no significant effect of general health checks on CVD (HR=1.11 (0.88; 1.41)) or all-cause mortality (HR=0.93 (0.75; 1.16)). When comparing invitees to the remaining Danish population, we found similar results for CVD (adjusted HR=0.99 (0.86; 1.13)) and all-cause mortality (adjusted HR=0.96 (0.85; 1.09)). Conclusion: We found no effect of general health checks offered to the general population on CVD or all-cause mortality. Trial registration number: NCT00145782; 2015-57-0002; 62908, 187.